Annotated bird sighting list for fall 1983 compiled by Tanya Bray - Bray, Tanyaet al (1983)
An annotated list of birds sighted by Tanya Bray and others. Includes a letter to Thomas Kent where Tanya Bray comments on the extensive reporting she made on Warblers, the fall IOU meeting, and the Sabine's Gull she saw at Saylorville. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1983. Epson - sheet feed